IMPLEMENTATION OF TEAM GAMES TOURNAMENT LEARNING METHOD TO IMPROVE WRITING ABILITY OF PROCEDURAL TEXT IN SMP MUHAMMADIYAH 10 SURABAYA - Waode Hamsia (LPPM Universitas PGRI Jombang, 2025)
This research aimed to examine the learning method of Team Games Tournament (TGT), which was to improve the writing ability of eighth grade students in SMP Muhammadiyah 10 Surabaya through the application of the Team Games Tournament (TGT) learning method in the teaching of procedures text. The researcher used Classroom Action Research (CAR) as the research design which was conducted in two cycles, with success indicators including at least 82% of students achieving scores above the Minimum Mastery Criteria of 75 and classes must have an average score of at least 80. The data collection techniques included observation, written tests, and documentation, while data was analyzed using descriptive quantitative. The results showed that the TGT method significantly improved students’ writing ability, as seen from the increase in average scores from 65 (pre-cycle) to 75 (cycle I) and 81 (cycle II), along with an increase in student achievement from 55.25% to 70.75% and finally 85.5%. This success was also supported by the modification of the tournament system from a competitive buzzer-style to a turn-based approach, which fostered a more equitable, participatory, and conducive learning environment. Thus, the TGT method applied adaptively has proven to be effective in improving the results of students' writing skills. The qualitative data based on the findings of student responses which showed that most students were interested and enjoyed the learning process through the application of the Team Games Tournament (TGT) learning method in the text of the teaching procedure.